No permission required : bringing S.T.E.A.M. to life in K-12 schools - Riley, Susan M., ....- (Westminster : Visionyst Press, 2014)
Are you ready to teach like an artist? To bring creativity to life in the classroom? In an educational era of test scores, teacher accountability, and shifting standards, many educators are worried that they don't have permission to encourage creative thinking and problem-solving in their schools. This book reminds us all that we don't need to permission to do what's best for children.